2020
DOI: 10.1038/s41598-020-72707-y
|View full text |Cite
|
Sign up to set email alerts
|

Body size and tube voltage dependent corrections for Hounsfield Unit in medical X-ray computed tomography: theory and experiments

Abstract: The purpose of this work is to present a body size and tube voltage dependent correction scheme for the Hounsfield Unit, HU, in medical X-ray Computed Tomography imaging. Boltzmann photon transport equation was employed to study X-ray interaction with bulk water in CT imaging. Experimentally measured X-ray output in body of phantoms and attenuation cross sections of water were employed in the derivation of beam intensity in X-ray imaging. A Somatom Emotion CT scanner from Siemens and electron density phantoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Notably, ex vivo bovine and swine tissue samples were scanned instead of human participants, which may have different tissue densities that influenced the internal calibration derived muscle density values. These samples do not account for differences in patient anatomy (i.e., patient size) which have been noted to impact resulting HU values [4547]. However, the internal calibration approach utilized here should be less dependent on patient characteristics as reference values are taken from the patient themselves, which should account for patient-specific alterations in x-ray attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ex vivo bovine and swine tissue samples were scanned instead of human participants, which may have different tissue densities that influenced the internal calibration derived muscle density values. These samples do not account for differences in patient anatomy (i.e., patient size) which have been noted to impact resulting HU values [4547]. However, the internal calibration approach utilized here should be less dependent on patient characteristics as reference values are taken from the patient themselves, which should account for patient-specific alterations in x-ray attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting the off-center variation characteristics of the approximately constant CT numbers and dose index CTDIv of the APEX scanner to the linearly increased CT numbers and CTDIv of the HD750 scanner led to the conclusion that the linearly enlarged sizes of SPR images without off-center corrections caused the linear increase of the CT numbers and CTDIv. It suggests that the body size and tube voltage dependent correction scheme [21] should be able to correct for the variations of CT numbers caused by the increased body sizes…”
Section: Discussionmentioning
confidence: 99%
“…A Revolution APEX and a Discovery HD750 CT scanner of General Electric (GE) were used to acquire images of an electron density phantom (model 062M, 27 cm × 33 cm) of computerized imaging reference systems (CIRS), Inc. (Norfolk, VA, USA) and an anthropomorphic phantom (model PBU-60, 165 cm in length and 50 kg in weight) of Kyoto Kagaku Co. (Kyoto, Japan), respectively. All tissue insert holes within the electron density phantom were filled with water balloons to mimic an abdomen section of human body [21]. Both phantom images were acquired under automatic tube current modulation (ATCM) mode using default noise index and under body (abdomen) bowtie filters.…”
Section: Methodsmentioning
confidence: 99%
“…though Zheng et al [27] suggested using body size and body depth, as well as tube-voltage dependent correction factors for the calculation of the "correct" HU in order to account for Rayleigh scattering of water.…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%